GREEN HUMAN RESOURCE MANAGEMENT AND ITS ROLE IN DRIVING SUSTAINABLE ORGANIZATION - Putra, Bayu Airlangga (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: Throughout the last decade, academics and business people have become interested in research on environmentally friendly workplaces. As a result, new fields of study such as green human resource management (GHRM) are gaining interest. Greening the workplace means greening common corporate tasks such as human resource management, marketing, operations, and supply chain management. GHRM plays a strategic role in helping companies to implement and develop strategic initiatives, as well as achieve corporate sustainability. In particular, green human resource management (GHRM) practices are also critical for generating organizational pride and motivating employees. Employees will feel proud of their company because they believe that their company supports community development, improves public health, and protects the environment and natural resources. This paper aims to examine in sufficient detail the GHRM concept followed by its various benefits for the business world, both at the organizational and individual levels. Design/methodology/approach: This paper is an in-depth review of several literatures regarding GHRM. Findings: A large number of experts and researchers agree that GHRM has an important role in realizing sustainable organizations while contributing to environmental protection from local to global scales. Research limitations/implications: This paper is conceptual and general in nature. Further, more in-depth empirical research still needs to be carried out, using both quantitative and qualitative approaches. Practical implications: There needs to be collaboration between academics and practitioners in developing the GHRM concept into various practical environmental management and corporate social responsibility (CSR) that are more concrete and specific according to their respective business sectors and communities. Originality/value: This paper is very relevant to remind business people that they are facing increasingly serious ecological challenges and there is not much time left to overcome them. Paper type: Conceptual paper